(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we introduce one interesting mathematical tool namely, (s, v)*-dense, and analyze its nature in a bigeneralized topological space. Further, we prove some properties of this set and give the relationship between (s, v)-dense and (s, v)*-dense sets. Finally, we give some applications for various sets defined in a bigeneralized topological space.